An Augmented Reality-Based Approach to Improving Science Concept Understanding Among Slow Learners - Yustina Bare; Cepi Safruddin Abdul Jabbar (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Slow learners generally experience difficulties in understanding abstract science concepts, requiring instructional media capable of presenting learning materials in a more concrete and interactive manner. One promising technology is Augmented Reality (AR). This study aimed to analyze the implementation of Augmented Reality in improving science concept understanding of slow learners on the human digestive system topic. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were three slow learner students in Grade VIII of SMP Negeri 3 Kongbeng, Indonesia. Data was collected through classroom observations, concept understanding tests, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of Augmented Reality significantly improved students' conceptual understanding. Students' scores increased from 40, 20, and 20 in the pre-action stage to 66, 60, and 60 in Cycle I, and further improved to 86, 80, and 80 in Cycle II, enabling all participants to achieve the minimum mastery criterion. In addition, students' learning activities improved from the good category to the very good category throughout the intervention. These findings indicate that Augmented Reality is an effective instructional medium for supporting inclusive science education by enhancing conceptual understanding among slow learner students.